Evaluation of masticatory performance and patient satisfaction for conventional and 3D-printed implant overdentures: a randomized crossover study - Mohamed Shady Nabil; Fatma Fathe Mahanna; Mohamed Moustafa Said (BMC, 2024)
Abstract Background This crossover clinical study aimed to evaluate and compare masticatory performance and patient satisfaction for patients rehabilitated with conventional heat-cured acrylic resin and 3D-printed mandibular implant overdentures retained with bar attachment. Materials and methods Sixteen completely edentulous healthy participants received new conventional dentures. In the mandible, four interforaminal implants were inserted. Following the stage of osseointegration, the bar was constructed in a trapezoidal configuration. Each patient randomly received the following overdentures using a crossover design: (1) conventional heat-cured acrylic resin overdenture and (2) 3D-printed overdenture (developed by scanning of mandibular conventional overdenture). The masticatory performance was assessed by conducting a two-colour mixing ability test at 5, 10, 20, 30, and 50 masticatory cycles. Moreover, the McGill Denture Satisfaction Questionnaire (MDSQ) was employed to assess patient satisfaction. Evaluation was performed after 3 months of using each overdenture. Paired sample t tests were used to compare the masticatory performance and MDSQ scores of patients for both prostheses. Results No significant difference in masticatory performance was reported between the two types of overdentures. Regarding patient satisfaction, only the esthetic aspect was significantly better for conventionally processed overdentures than for printed overdentures. Insignificant differences were observed regarding other MDSQ items between the two overdentures. Conclusion Within this clinical study, 3D-printed implant overdentures showed promising results in terms of chewing efficiency and patient satisfaction compared to conventionally fabricated implant overdentures. Trial registration Retrospectively registered at www.clinicaltrials.gov : NCT06148727.(28/11/2023).